The Role of Interdisciplinary Healthcare Teams in Mitigating Malnutrition Among Vulnerable Populations: Review of Collaborative Strategies Among Dietitians, Pharmacists, Dentists, and Social Workers - Alzahrani , Khaled Bkeet Abdullah; Alqattan, Abdulmuhaymin Hani; Alharbi, Khaola Hmood; Alhassoon, Amal Hamad; Alrehaili, Sahal Mohamed; Alkuraiea , Sharoog Abdulrahman; Ashri, Mwaed Abdulrazaq; Alharshani , Abdulrahman Atiah Allah; Alqahtani , Saeed Mana; Alharbi, Khaled Nasser; Kadi, Effat Adnan; Almutairi, Badreia Mater; et al. (Journal of Ecohumanism, 2024)
Background: Malnutrition, particularly undernutrition, poses significant challenges in healthcare settings, adversely affecting patient outcomes, including increased morbidity and mortality. Effective management of malnutrition requires a collaborative approach among healthcare professionals, including dietitians, pharmacists, dentists, and social workers. Methods: This systematic review employed a comprehensive search strategy across multiple databases, including MEDLINE, to identify primary studies that investigated interdisciplinary collaboration in nutritional care for vulnerable populations. The review focused on the roles and contributions of various healthcare disciplines in addressing malnutrition and enhancing patient outcomes. Results: The findings indicate that interdisciplinary healthcare teams significantly improve nutritional management by promoting effective communication and collaboration among diverse professionals. Key stakeholders, including patients and their families, play crucial roles in these collaborative efforts. The analysis revealed that while the implementation of multidisciplinary care models is endorsed, there remains a lack of comprehensive understanding regarding the processes that facilitate effective collaboration and the specific roles of each discipline. Conclusion: The study concludes that fostering interdisciplinary collaboration is essential for optimizing nutritional care in vulnerable populations. Policymakers and healthcare organizations should prioritize the development of frameworks that enhance communication, role clarity, and shared responsibilities among healthcare providers to address malnutrition effectively. Further research is needed to explore the dynamics of interdisciplinary teamwork in nutritional care and its impact on patient outcomes.